Assessing regulating and provisioning ecosystem services in a contrasting tropical forest landscape. (May 2016) - Alamgir, Mohammed; Turton, Stephen M.; Macgregor, Colin J.; Pert, Petina L.
Highlights: Eight ecosystem services (ES) were estimated and their hotspots were identified. Rainforests possess a very high capacity to supply multiple ES. Upland rainforests are the hotspots of multiple ES supply. The rehabilitated forests may provide some ES nearly equivalent to the rainforest. ES supply from the sclerophyll forests are lower, most likely due to their lower structural diversity. Abstract: Ecosystem services are the bridge between nature and society, and are essential elements of community well-being. The Wet Tropics Australia, is environmentally and biologically diverse, and supplies numerous ecosystem services. It contributes to the community well-being of this region, Australian national economy and global climate change mitigation efforts. However, the ecosystem services in the region have rarely been assessed undermining strategic landscape planning to sustain their future flow. In this study, we attempted to: (i) assess the quantity of five regulating ecosystem services – global climate regulation, air quality regulation, erosion regulation, nutrient regulation, and cyclone protection, and three provisioning ecosystem services – habitat provision, energy provision and timber provision across rainforests, sclerophyll forests and rehabilitated plantation forests; (ii) evaluate the variation of supply of those regulating and provisioning ecosystem services across environmental gradients, such as rainfall, temperature, and elevation; (iii) show the relationships among those ecosystem services; and (iv) identify the hotspots of single and multiple ecosystem services supply across the landscape. The results showed that rainforests possess a very high capacity to supply single and multiple ecosystem services, and the hotspots for most of the regulating and provisioning ecosystem services are found in upland rainforest followed by lowland rainforest, and upland sclerophyll forest. Elevation, rainfall and temperature gradients along with forest structure are the main determinant factors for the quantity of ecosystem services supplied across the three forest types. The correlation among ecosystem services may be positive or negative depending on the ecosystem service category and vegetation type. The rehabilitated plantation forests may provide some ecosystem services comparable to the rainforest. The results demonstrated disturbance regimes (such as tropical cyclones) may have influenced the usual spatial trend of ecosystem service values. This study will assist decision makers in incorporating ecosystem services into their natural resource management planning, and for practitioners to identify the areas with higher values of specific and multiple ecosystem services.